1998
DOI: 10.1097/00007632-199801010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Lactate Concentrations Measured in Vivo in the Intervertebral Discs of Patients With Scoliosis and Back Pain

Abstract: Concentrations of metabolites depend on cellular activity and on transport of the metabolite between the blood supply and the cell. The correlation between degeneration and nutrition cannot be determined only from metabolite concentrations; measurements of metabolic activity and nutrient transport rates also are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
193
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(208 citation statements)
references
References 27 publications
15
193
0
Order By: Relevance
“…NP cells are unique in their ability to adapt to their physiological environment, defined by low‐oxygen and nutrient levels (Bartels, Fairbank, Winlove, & Urban, 1998). In a recent study, Choi et al (2016) showed that NP cells activate autophagy under hypoxic conditions through a noncanonical, HIF1A, and mTOR‐independent mechanism and that this activation of autophagy was required for long‐term NP cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NP cells are unique in their ability to adapt to their physiological environment, defined by low‐oxygen and nutrient levels (Bartels, Fairbank, Winlove, & Urban, 1998). In a recent study, Choi et al (2016) showed that NP cells activate autophagy under hypoxic conditions through a noncanonical, HIF1A, and mTOR‐independent mechanism and that this activation of autophagy was required for long‐term NP cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the severe degenerative changes in the NP, our data using both mouse models show that FOXO deletion led to cell loss and ossification in the cartilaginous EP. The EP has a pivotal role in regulating the nutritional status of the IVD and the age‐related decrease in EP permeability due to ossification has been suggested as a contributing factor in IDD (Bartels et al, 1998; Bernick & Cailliet, 1982; Wang, Battie, Boyd, & Videman, 2011). It is thus likely that reduced EP permeability secondary to EP calcification significantly contributes to the severe degeneration observed in FOXO‐deficient IVD.…”
Section: Discussionmentioning
confidence: 99%
“…In disc cells, activation of the stress sensing HSF-1 complex could be triggered by several mechanisms, which result in Hsp expression [21]. ECM degeneration may lead to an environmental trigger such as exposure of the disc cells, particularly in extruded or sequestrated states, to environmental conditions (including hydrostatic loading or oxygen tensions) different from those experienced by cells in intact discs [5,7]. Alternatively, a stress response could also be initiated by a proteotoxic stress: in this case, the presence of abnormal ECM components in the cytoplasm, such as incorrectly folded or denatured proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1 NP is also a completely aneural and avascular tissue; hence the microenvironment is physiologically hypoxic. [2][3][4][5] NP cells adapt to this hypoxic niche by modulating a key transcription factor, HIF1A (hypoxia inducible factor 1 a subunit), to promote cell survival, matrix synthesis, and to regulate glycolytic metabolism. [6][7][8][9][10][11][12][13] A recent study using NP-specific conditional Hif1a knockout mice also shows that HIF1A is required for postnatal NP cell survival in vivo.…”
Section: Introductionmentioning
confidence: 99%